O necessário, o possível e o impossível: Uma leitura do papel das políticas públicas diante dos limites à coordenaç\~ao de grandes investimentos na periferia metropolitana Fluminense - Bruno Leonardo Barth Sobral (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– Over the last decades, the challenge of giving support to national economic growth process has become an undisputed issue. Since the second term of the Lula government, the theme of resumption of investment was imposed. In particular, the State of Rio de Janeiro benefited from a cycle of large investments, resuming the debate on the strength of its centrality - in this case, "capitalidade". This paper discusses what lessons about state action teaches that experience on the periphery of Metropolitan Region of Rio de Janeiro specifically from the realization of Thyssenkrupp CSA, Comperj, Promef and Metropolitan Arch. In particular, it seeks to question the authenticity of a certain "state capitalism" on the role of public policies in the coordination of decisions.
Keywords: E22; E61; E65; H54; L21; L25; O11; O14; O22; 330; state capitalism; public policy; Thyssenkrupp CSA; Comperj; Promef; Metropolitan Arch; Rio de Janeiro